2022
DOI: 10.1186/s12885-022-10203-4
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strength is associated with fracture risk obtained by fracture risk assessment tool (FRAX) in women with breast cancer

Abstract: Background Women with breast cancer are at risk for the development of sarcopenia and occurrence of fractures. The initial and periodic screening of these conditions can prevent the risks of disability, poor quality of life, and death. The present study investigated the association between sarcopenia phenotypes and fracture risk, assessed by the Fracture Risk Assessment Tool (FRAX) in women with breast cancer. Methods Cross-sectional study. It incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Alajlouni et al 45 demonstrated that measurement of muscle strength and physical performance further improves prediction of osteoporotic fracture risk compared with established scoring tools alone. Similar findings have been described for breast cancer patients 46 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Alajlouni et al 45 demonstrated that measurement of muscle strength and physical performance further improves prediction of osteoporotic fracture risk compared with established scoring tools alone. Similar findings have been described for breast cancer patients 46 …”
Section: Discussionsupporting
confidence: 89%
“…Similar findings have been described for breast cancer patients. 46 We was continuously reported, but most patients were aware that they could positively influence these symptoms by performing PEP, which is essential for patients' self-efficacy and for reducing fear of pain/ injury due to movement. In line with this observation, patients performing PEP were also more likely to discontinue pain medication.…”
Section: Individual Physical Fitnessmentioning
confidence: 99%
“…In frail elderly patients, KA may protect against hip fracture by reducing the occurrence of falls. On the other hand, within the first month after KA, muscle strength is often decreased, which can elevate fracture risk [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenia may lack specific clinical features; patients with it may present with weakness, difficulty walking, slow gait, and thin and weak limbs ( Aoki et al, 2022 ). Sarcopenia may increase the risk of falls and fractures ( de Almeida Marques Bernabe et al, 2022 ), decrease the quality of daily living activities, and relate to many comorbidities such as cardiac disease ( Loh et al, 2022 ), diabetes ( Jun et al, 2022 ), and cognitive impairment ( Noda et al, 2022 )—although these symptoms can be easy to ignore ( Malmstrom et al, 2016 ; Mijnarends et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%